Identification of highly potent α-glucosidase inhibitory and antioxidant constituents from Zizyphus rugosa bark: enzyme kinetic and molecular docking studies with active metabolites - Jirapast Sichaem; Thammarat Aree; Kiattisak Lugsanangarm; Santi Tip-pyang (Taylor & Francis Group, 2017)
Context: Previous studies have shown that extracts of Zizyphus rugosa Lam. (Rhamnaceae) bark contained phytoconstituents with antidiabetic potential to lower blood glucose levels in diabetic rats. However, there has been no report on the active compounds in this plant as potential antidiabetic inhibitors. Objective: We evaluated the α-glucosidase inhibitory and antioxidant activities of Z. rugosa extract. Moreover, the active phytochemical constituents were isolated and characterized. Materials and methods: The α-glucosidase inhibition of crude ethanol extract obtained from the bark of Z. rugosa was assayed as well as the antioxidant activity. Active compounds (1-6) were isolated, the structures were determined, and derivatives (2a-2 l) were prepared. All compounds were tested for their α-glucosidase inhibitory (yeast and rat intestine) and antioxidant (DPPH) activities. Results: The active α-glucosidase inhibitors (1-6) were isolated from Z. rugosa bark and 12 derivatives (2a-2 l) were prepared. Compound 2 showed the most powerful yeast α-glucosidase inhibitory activity (IC50 16.3 μM), while compounds 3 and 4 display only weak inhibition toward rat intestinal α-glucosidase. Moreover, compound 6 showed the most potent antioxidant activity (IC50 42.8 μM). The molecular docking results highlighted the role of the carboxyl moiety of 2 for yeast α-glucosidase inhibition through H-bonding. Discussion and conclusions: These results suggest the potential of Z. rugosa bark for future application in the treatment of diabetes and active compounds 1 and 2 have emerged as promising molecules for therapy.